PENGARUH PELATIHAN DAN DISIPLIN KERJA TERHADAPKINERJA KARYAWAN - SAFITRI, ERMA (Jurnal Ilmu Manajemen (JIM), 2013)
The increasing of hi-technology requires every one to beable to follow these developments, not least the human resources incompanies. That is because many companies are becoming based technology. The amendment requires individuals to think creatively, work fast, and right to become a competence person. This studyaims to examine and analyze the influence of the training and workdiscipline on employee performance. With a sample of 38 employeesat the Apron Move Control Devision PT. Angkasa Pura 1(Persero)International Airport Branch Juanda-Surabaya, using SPSS18.0statistical software. The results showed that the training and disciplineof work has a positive effecton employee performance.Keywords: training, work discipline, and employee performance.